ANALISIS YURIDIS TERHADAP TINDAK PIDANA KERUSAKAN LINGKUNGAN HIDUP YANG DI AKIBATKAN OLEH PERTAMBANGAN PASIR ILLEGAL DI KECAMATAN DATUK BANDAR TIMUR KOTA TANJUNGBALAI - Muhammad Alfarizi Sirait; Syahrul Bakti Harahap (Sekolah Tinggi Pariwisata Mataram, 2022)
This research was conducted in Tanjungbalai City, precisely in Datuk Bandar Timur District, this study aims to determine the factors behind the occurrence of illegal sand mining and the efforts that can be made to overcome illegal sand mining in Datuk Bandar Timur District Tanjungbalai City.Data obtained through data Sources of data needed in this study are primary data and secondary data. The legal research method is descriptive analytical, where data will be obtained from reading and analyzing materials and written interviews by illegal mining actors in the Datuk Bandar Timur District, Tanjungbalai City. The results of this study explain how legal accountability for perpetrators of criminal acts of environmental damage caused by illegal sand mining and to find out the factors behind the occurrence of illegal sand mining and the efforts that can be made to overcome illegal sand mining in Datuk Bandar Timur District, Kota Tanjung Balai. Through the results of the author's interview with the perpetrators, the community and the Semula Jadi village apparatus, he explained that there were five factors that caused the rise of illegal sand mining in Datuk Bandar Timur District, including (1). Natural resource opportunity factor (2). The demand factor for material needs (3). The factor of the lack of supervision by the government (4) The factor of the absence of socialization of regulations on mining (5). The difficulty factor in obtaining an IUP. The efforts that can be made to overcome the illegal sand mining are (1). Conducting socialization to the community (2). Supervise the vicinity of the mining site (3). Issue local regulations on mining.